The extraction of lignin from empty fruit bunch fiber via microwave-assisted acid hydrotrope solvent - Jafri, N. F.; Yaakob, M. N. A.; Rasidi, Roslan (Universiti Malaysia Pahang, 2021)
Lignin is a sub-product from lignocellulose apart from cellulose and hemicellulose that produced from empty fruit bunch fiber (EFB). Lignin has low solubility and reactivity due to its bulky macromolecule structre. Being one of the wastes that being generated in massive amount, many alternatives has been taken to transform lignin into valuable products. To do so, many reactions are needed for the lignin to go through. In this study, lignin will be extracted from empty fruit bunch (EFB) with the aid of acid hydrotrope concentration of 30 % and microwave assisted with various extraction heating time and temperature. Characterization of lignin is done using Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA), Differential Scanning Calorimetry (DSC) and Nuclear magnetic resonance (NMR) while Scanning Electron Microscopy (SEM) and X-ray Powder Diffraction (XRD) used to characterize residues. The highest percentage of lignin yield and its purity obtained are 19.47 % and 96.63 % with the reaction time and temperature of the microwave is 30 minutes and 90 °C. From Fourier Transform Infrared Spectroscopy (FTIR), a wide band at 3430.09 cm-1 and 3413.45 cm-1 are observed due to O-H stretching vibration. As for peak at 1123.17 cm-1 and 1051.26 cm-1, it correspond to syringyl and guaicyl unit in both lignin and raw EFB. As for Thermogravimetric analysis (TGA), it shows that lignin decomposes slowly compared to raw EFB due to the aromatic structure of lignin that is very stable, therefore leading to difficulty of decomposing while from Differential Scanning Calorimetry (DSC), after removing cellulose and hemicellulose, glass transition temperature (Tg) obtained from lignin DSC spectroscopy is 193.05 °C at heat flow of 1.15 mW/mg. Next, from Nuclear magnetic resonance (NMR) spectroscopy, the signals observed around 6.5 – 8.0 ppm indicate aromatic H in syringyl and guaiacyl unit only at lignin spectra while at 3.3 – 4.0 ppm, raw EFB has an intense peak compared to lignin which attribute to methoxyl group. When the residue of the lignin as well as the raw EFB powder is characterized using X-ray Powder Diffraction (XRD), the crystallinity index of the lignin with reaction time and temperature of the microwave 30 minutes and 90 °C is the highest, 69.28 %. As a conclusion, an admissible percent of lignin yield and purity is able to be obtained with addition of acid hydrotrope depending on the variables. From the spectroscopies characterization, it is proved that lignin characteristics and properties are compatible for the production of new and value added products.